Odpowiedź:
[Przy tego typu granicach dzielimy licznik i mianownik przez najwyższą potęgę mianownika]
lim n → ∞ [(16n² - 8n + 5):n]/[(8n - 6):n] =
= lim n → ∞ (n - 8 - 5/n)/(8 - 6/n) =
= (+ ∞ - 8 - 0)/(8 - 0) = + ∞/8 = + ∞
Szczegółowe wyjaśnienie:
Oblicz granicę (1n), lim n -> ∞ (16n ^ 2 - 8n + 5)/(8n - 6) =
[Przy tego typu granicach dzielimy licznik i mianownik przez najwyższą potęgę mianownika]
lim n → ∞ [(16n² - 8n + 5):n]/[(8n - 6):n] =
= lim n → ∞ (n - 8 - 5/n)/(8 - 6/n) =
= (+ ∞ - 8 - 0)/(8 - 0) = + ∞/8 = + ∞